POLA ASUH ORANGTUA PADA GENERASI ALPHA DI RA MUSLIMAT DARUS SALAM HARJOKUNCARAN-MALANG - Rohmawati, Afifatu; Rosida, Cholifatur (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2025)
The Technological advancement is increasingly complex and rapidly influencing society, especially among youth and children. Managing the current level of technological and informational growth appears nearly impossible. This development pertains to contemporary children, commonly referred to as the alpha generation, which includes those born between 2013 and 2025. The majority of alpha generation members are offspring of Millennials and grandchildren of baby boomers. This study focuses on analyzing: 1) parenting styles, 2) parental regulation of alpha generation children regarding technology use in the digital age, and 3) the effects of digital technology usage on the social development of alpha generation children. The analysis integrates conceptual frameworks with real-world social contexts. To thoroughly and comprehensively explore the aforementioned issues, the researcher employed field research methods alongside a descriptive analysis approach, which effectively provides factual information and data concerning parenting styles. The collected data was then analyzed to address the identified problems. The research findings indicated that the predominant parenting style observed is democratic parenting. Parents maintain daily supervision over their children, particularly when they are engaging with cellphones or gadgets. Parents and educators leverage digital technology to create more enjoyable learning experiences for children. The study concluded that parental roles in monitoring technology use involve establishing strict and disciplined boundaries. Additionally, parental support for the alpha generation’s learning process via technology allows for the selection of educationally valuable learning concepts.